Islamic Religious Education Teacher Strategy in Instrumenting Values Multicultural of SMP Negeri 2 Merauke South of Papua - Akbar; Talabudin Umkabu; Siti. Rokhmah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This research is field research which is motivated by the emergence of student problems and teacher problems in instilling multicultural values in students at SMP Negeri 2 Merauke, South Papua, which is quite diverse both in terms of class, customs, tribe, race, ethnicity, language as well as culture and religion such as; Islam, Protestant Christianity, Catholic Christianity, Hinduism and Buddhism in schools. The aim of this research is to find out what strategies are used by Islamic religious education teachers and to find out the supporting and inhibiting factors faced in implementing strategies for instilling multicultural values in students at SMP Negeri 2 Merauke, South Papua. In this research, the author used a descriptive qualitative research method using a methodological and pedagogical approach. This type of research is qualitative research taking the research location at SMP Negeri 2 Merauke, South Papua. Data collection was carried out by means of observation, interviews and documentation with data analysis using Miles Huberman, namely reducing data, presenting data, verifying or drawing conclusions where real data was directly collected about the strategies of Islamic religious education teachers in instilling multicultural values in students in junior high schools. Negeri 2 Merauke, South Papua. From the results of this research, it shows that there are several steps taken by Islamic religious education teachers related to the strategies used to instill multicultural values in students at SMP Negeri 2 Merauke, South Papua, namely by; Appropriate lesson plans, PBL (Problem Based Learning) and PAIKEM (Active, Innovative, Creative, Effective and Fun Learning) models and extracurricular activities. The multicultural values that have been instilled include; inclusive values, humanist values, tolerance values, democratic values and brotherhood values. The supporting factors are the school climate, infrastructure, the role of teachers, school programs and activities as well as interactions between components in the school so that the instillation of multicultural values in students can run well and smoothly. The inhibiting factors are the lack of teacher communication and lack of student discipline.